Abattoir waste use in livestock diets: Uganda’s current situation - Mwesigwa, R; Migwi, PK; King’ori, AM; Onjoro, PA (International Journal of Agricultural Research, Innovation and Technology, 2020)
In this study, we investigated the various ways slaughter wastes are utilized, problems encountered in order to give insights in future prospects of abattoir wastes as livestock feeds. A total of 100 abattoir workers were interviewed through semi-structured questionnaires covering Kampala, Wakiso and Mukono districts in Uganda. Results revealed that majority of abattoir work force were middle-aged adults between 30-45 years contributing 37% of total workers. There was a significant association between abattoir workers responses in relation to the proportion of livestock slaughtered (Chi square 147.55; df =2; p<0.0001) in the abattoirs. With reference to cattle, 1.06 and 1.01 more sheep and goats were slaughtered respectively in the dry season in comparison to the wet season. Blood was mostly disposed as animal feed ingredient (blood meal) by 40% of the respondents while rumen contents were mostly sold as manure by 59% of the respondents. Only 16% of the respondents processed rumen contents for livestock feeding. 92.3% of bones were sold for dog feeding while 7.7% of bones were processed for livestock feed ingredients. Polythene bags were reported the biggest contaminants found in slaughter wastes. Stench from slaughter wastes contents was the biggest problem encountered with handling of waste products by (62%) of the respondents. The handling of abattoir wastes was still rudimental at most abattoirs as envisaged by lack of proper handling facilities at the abattoirs. There is need for regular enforcements to ensure proper abattoir waste disposal mechanisms for enhanced livestock use. Int. J. Agril. Res. Innov. Tech. 10(1): 129-134, June 2020